Analisa Perbandingan Manajemen Proses Multitasking pada Sistem Operasi Windows dan Linux - Ghufron Malik; Kholid Wahyudi; Febri Tri Arie Sakti; Abdul Ghofar; Abdul Halim Anshor (Pusat Riset dan Inovasi Nasional, 2024)
Multitasking is a crucial feature in operating systems, allowing multiple processes to run simultaneously something that is very important in modern computing. This study explores the comparison between two major operating systems, Windows and Linux, especially in the aspects of process scheduling, CPU usage efficiency, and memory management. Using a literature study and experimental approach, the results show that Linux tends to be more efficient in managing multitasking with the Completely Fair Scheduler (CFS) algorithm, while Windows is superior in stability for graphical applications. These results provide guidance for users in choosing an operating system that suits their multitasking needs.